Probiotic microorganisms involved in cassava fermentation for Gari and Attiéképroduction - Aly, SAVADOGO; Flibert, GUIRA; Francois, TAPSOBA (JOURNAL OF ADVANCES IN BIOTECHNOLOGY, 2016)
Several fermented foods and beverages for human nutritionthat incorporate lactic acid bacteria and others beneficial microorganisms are produced throughout the world. Lactic acid bacteria (LAB) are widely distributed in nature and occur as natural microflora in many fermented foods (fermented milk, cereal fermented food, fermented fruit products, fermented roots products like cassava and others). This study gave characteristics, nutritional, Health and functional properties of probiotics microorganisms involved in cassava fermentation forGariand Attiéké production production. During cassava fermentation for Gariand Attiéké production many microorganisms with probiotic properties were involved and gave benefic properties. Lactic acid bacteria and yeast involved in food fermentation or production particular in cassava products may possess probiotic properties.Probiotics may have potential roles, as natural barriers to pathogens associated with intestinal disease with functional role.Probiotic microorganisms role and importance in cassava fermentation for Gariand Attiéké production for healthy nutrition for consumers were developed in this work.